The Analysis of Students’ Creative Thinking Skills through the Implementation of the Project Based Learning Model in Social Studies Learning - Prihatin, Ririn (International Journal Pedagogy of Social Studies, 2021)
This research is motivated by the lack of creative thinking skills of students in social studies learning. This is because learning is still dominated by teachers. This research aims at describing the Project Based Learning model to encourage creative thinking, the planning of Project Based Learning, the implementation strategies of ProjectBased Learning, and the solutions to obstacles in developing creative thinking. The approach employed in this research was a qualitative approach with descriptive methods. The data were collected through interviews and documentation studies. Thesubjects of this study were a social studies teacher and 25 students in class VII-E. Based on the research results, it could be seen that 1) the implementation of the Project Based Learning model had been able to develop students’ creative thinking skills, which could be seen from the results of the projects they had done; 2) the planning in implementing the Project Based Learning model had been wellprepared and could develop students’ creative thinking; 3) the process of implementing the Project Based Learning was carried out in accordance with the syntax of the Project Based Learning model itself, starting from asking basic questions to evaluating experiences; 4) The obstacles faced were class management, planning learning time, students who were not able to fathom the aims and objectives to be conveyed, and students who needed to be given an overview of the example projects they were going to work on.